TURN TAKING STRATEGIES IN CLASSROOM INTERACTION - Syafar, Dian Noviani; Putri, Dian Mega; Autila, Rani (TELL - US JOURNAL, 2023)
This research is to investigate the conversational strategies employed by teacher-students in classroom interaction from conversational analysis (CA) perspective. This research employs a documentary method of interpretation in order to seek answer(s) to the research question. Specifically, Sacks, Schegloff and Jefferson’s (1974) model of conversation analysis is adopted to explore turn-taking strategies used in classroom interaction. The data was taken based on the recording of classroom interaction in one of the senior high school in Padang. The analysis reveals that interaction between teacher and students employed a variety of turn-taking strategies; taking the floor and holding the floor. As the findings, the researcher finds out that the teacher mostly dominates to start the conversation and raises up the starter verbal filler.  On the other hand, the students are more interruptive and put silences to hold the floor.